Asymmetric synthesis of (+)-stagonolide C and (-)-aspinolide A via organocatalysis - Shelke, Anil M.; Rawat, Varun; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A new enantioselective synthesis of two important fungal metabolites, (+)-stagonolide C and (-)-aspinolide A, has been described from readily available raw materials. Praline catalyzed asymmetric alpha-aminooxylation and Jorgensen's epoxidation of aldehydes are the key reactions employed in the introduction of chirality. The formation of the 10-membered lactone core structure was finally accomplished via Steglich esterification and ring closing metathesis reactions. (C) 2012 Elsevier Ltd. All rights reserved.

Efficient one pot regioselective synthesis of a 3,3 `-spiro-phosphonylpyrazole-oxindole framework via base mediated [1,3]-dipolar cycloaddition reaction of the Bestmann-Ohira reagent with methyleneindolinones - Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2015)
A one pot, highly regioselective synthesis of racemic 3,3'-spiro-phosphonylpyrazole-oxindole by 1,3-dipolar cycloaddition of an in situ generated anion of dialkyl 1-diazomethylphosphonate from the Bestmann-Ohira reagent (BOR) & methyleneindolinones has been developed. The synthesis affords the highly functionalized pyrazole scaffolds in good yields with excellent regioselectivity under mild reaction conditions within a short reaction time.

Efficient organocatalytic route for asymmetric total synthesis of stagonolide F - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron Letters, 2015)
A stereoselective total synthesis of Stagonolide F (98% ee) is described employing asymmetric alpha-aminooxylation, Jorgensen's asymmetric epoxidation, Brown asymmetric allylation, Steglich esterification and ring closing metathesis as key steps. The use of organocatalytic alpha-aminooxylation and Jorgensen's asymmetric epoxidation of aldehydes for the introduction of chirality makes this approach more attractive. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Aminooxylation; Jorgensens's asymmetric epoxidation; Macrolide; Ring-closing metathesis; Total synthesis

Fluoride-assisted synthesis of 1,4,5,6-tetrahydropyridazines via [4+2] cyclodimerization of in situ-generated azoalkenes followed by a C-N bond cleavage - Shelke, Anil M.; Suryavanshi, Gurunath (Organic Letters, 2016)
An unexpected CsF-assisted C-N bond cleavage was exploited to synthesize highly functionalized and biologically important 1,4,5,6-tetralrydropyridazine derivatives from alpha-halo N-acylhydrazohes in excellent yields. The extrusion of nitrogen and the [4 + 2] cycloaddition between in situ-generated azoalkenes is a key reaction in the process. The identified methodology is suitable for synthesizing a wide variety of analogues of tetrahydropyridazines, which are prevalent in many medicinally important small molecules. The reaction conditions are mild, high-yielding, and amenable for the gram scale.

Formal synthesis of pinolide via L-proline-catalyzed sequential alpha-aminooxylation, horner-wadsworth-emmons olefination and sharpless asymmetric dihydroxylation - Shelke, Anil M.; Suryavanshi, Gurunath (Tetrahedron-Asymmetry, 2016)
A convergent, formal enantioselective synthesis of pinolide, a new nonenolide, has been achieved with high enantiomeric purity (99% ee) starting from readily available raw materials. The main highlight of the synthetic strategy is the application of L-proline catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination of an aldehyde, Sharpless asymmetric dihydroxylation and Steglich esterification as the key steps for the construction of a key chiral intermediate of the target molecule. (C) 2016 Elsevier Ltd. All rights reserved.

Efficient Sn(II)-catalyzed one-pot synthesis of a 3-substituted azetidine-2,4-dione framework - Chavan, Santosh S.; Supekar, Mrudul V.; Burate, Pralhad A.; Rupanwar, Bapurao D.; Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2017)
A novel Sn(II)-catalyzed tandem cyclization reaction of aromatic aldehydes with ethyl cyanoacetate has been achieved to afford a series of 3-substituted azetidine-2,4-diones in good to excellent yields. This protocol provides straightforward access to construct the azetidine core through sequential Knoevenagel condensation, hydration and the C-N cyclization reaction.

Metal-free annulation of β-acylamino ketones: facile access to spirooxazolines and oxazolines via oxidative C–O bond formation - Chavan, Santosh S.; Rupanawar, Bapurao D.; Kamble, Rohit B.; Shelke, Anil M.; Gurunath Suryavanshi (Organic Chemistry Frontiers, 2018)
A metal-free annulation reaction of β-acylamino ketone derivatives has been reported for the synthesis of a group of functionalized spirooxazolines and oxazolines in good to excellent yields. The reaction proceeds via phenyliodine(III) diacetate (PIDA)-mediated oxidative C–O bond formation in the presence of BF3–OEt2. The mild reaction conditions, broad substrate scope, simple execution and synthetic potential of the products make this novel protocol very attractive.